2019
DOI: 10.1111/jon.12647
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Gray and White Matter Involvement in Anorexia Nervosa Evaluated by T1, T2, and T2* Mapping

Abstract: BACKGROUND AND PURPOSE Changes in the brain composition of anorexics could potentially be expected, opening the door to new imaging approaches where quantitative and qualitative MRI have a role. Our purpose was to investigate anorexia‐related brain dehydration and myelin depletion by analyzing T1, T2, and T2* relaxation times of different brain structures in anorexics and controls. METHODS Thirty‐eight anorexic female patients (mean age, 26.2 years; age range, 16.2‐48.7 years; mean BMI, 14.5 kg/m2; BMI range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…The use of a high-resolution MRI scanner allowed for the first time to use T 1 values as a proxy to investigate depth-dependent intracortical myelin organization in-vivo. Our results are consistent with previous findings of reduced myelin concentration in AN 27,44 , and go beyond these, showing that such a deficit is widespread and mainly affects the outer depth-levels dependent intracortical myelin organization. Travis and colleagues 27 reported a relationship between decreased fractional anisotropy (FA, defined as a marker of WM integrity) and decreased relaxation time R1 (considered as an index of myelin content) in AN adolescents.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The use of a high-resolution MRI scanner allowed for the first time to use T 1 values as a proxy to investigate depth-dependent intracortical myelin organization in-vivo. Our results are consistent with previous findings of reduced myelin concentration in AN 27,44 , and go beyond these, showing that such a deficit is widespread and mainly affects the outer depth-levels dependent intracortical myelin organization. Travis and colleagues 27 reported a relationship between decreased fractional anisotropy (FA, defined as a marker of WM integrity) and decreased relaxation time R1 (considered as an index of myelin content) in AN adolescents.…”
Section: Discussionsupporting
confidence: 93%
“…Whereas in our study higher T 1 values were found in patients with AN, in a recent study 44 performed with a 3 T MRI scanner an opposite pattern emerged, i.e., patients with AN showed lower T 1 relaxation times (i.e. time constant indicating how long the protons need to return to the equilibrium state 41 ) than controls in both gray matter and WM.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…MRF has several advantages over other MRI approaches, [7][8][9][10] allowing for superior quantification. Since the quantification of T1 and T2 values is obtained simultaneously using MRF, the effects of motion between scans are mitigated.…”
Section: Discussionmentioning
confidence: 99%
“…Matching the fingerprints to a database of simulated signals (dictionary) allows for parameter mapping of relaxation parameters, including T1, T2, and T2*. 5,6 Compared with other T1 and T2 mapping methods using conventional MRI approaches, [7][8][9][10] MRF is reported to have superior performance with regard to both accuracy and efficiency. 11 Recently, MRF became commercially available for joint T1 and T2 mapping.…”
Section: Introductionmentioning
confidence: 99%